Antagonist elastic interactions tuning spin crossover and LIESST behaviours in FeII trinuclear-based one-dimensional chains. Issue 24 (31st October 2022) - Pittala, Narsimhulu; Cuza, Emmelyne; Pinkowicz, Dawid; Magott, Michał; Marchivie, Mathieu; Boukheddaden, Kamel; Triki, Smail
Abstract : A new 1-D spin SCO coordination polymer based on Fe II trinuclear units covalently linked by a flexible coligand has been reported as an unusual platform and model system for experimental study on the origin of the step-like feature in 1-D systems. Abstract : A new 1D coordination polymer, [Fe3 (μ2 -bntrz)6 (bntrz)2 (μ2 -tcnsme)2 ](tcnsme)4 ·4H2 O (1·4H2 O ), based on [Fe3 (μ2 -bntrz)6 ] trinuclear units covalently linked by symmetric double cyanocarbanion coligands involving 12-membered metallacycles has been prepared and characterised. The crystal structure of 1·4H2 O revealed a trinuclear fragment, [Fe3 (μ2 -bntrz)6 (bntrz)2 (μ2 -tcnsme)2 ] 4+, composed of a central Fe II ion (Fe1) and two external metal ions (Fe2), similar to that described for the discrete trinuclear complex [Fe3 (μ2 -bntrz)6 (tcnset)6 ] (2 ) previously reported. Magnetic studies of 1·4H2 O showed a continuous gradual decrease of the magnetic signal, characteristic of the presence of a complete one-step gradual HS to LS transition ( T 1/2 = 281 K) different from the abrupt one described for 2 . This difference has been attributed to the presence of competing ferro- and anti-ferroelastic interactions, induced, respectively, by the intra- (μ2 -bntrz) and inter-trimer (μ2 -tcnsme) covalent links in 1·4H2 O . TGA and powder X-ray diffraction analyses revealed that 1·4H2 O shows a complete and reversible "dehydration (1 )/hydration (1·4H2 O )" process that occurs, respectively, by heating 1·4H2 O at 370 K and by soaking in water the dehydrated sample (1 ). The magnetic behaviour of 1 exhibits a two-step SCO transition at ca. 245 K. Thanks to the combined magnetic and vibrational infrared data allowing correct extraction of the contribution of the two Fe II active centres (one central Fe1 and two external Fe2 ions), the first step (370–245 K) was attributed to a concomitant HS/LS switching of the central Fe1 and a half of the Fe2 ions and the second one, occurring below 245 K, was attributed to the HS/LS transition of the remaining HS state among the randomly distributed Fe2 external ions. Photomagnetic experiments have been performed for both hydrated (1·4H2 O ) and dehydrated (1 ) phases. As expected from their thermal transition temperatures, no photomagnetic response was observed for 1·4H2 O at 638 nm nor at 450 nm, while the dehydrated phase (1 ) shows an increase of the magnetic moment, reaching a maximum of 1.4 cm 3 K mol −1 at 22 K, followed by the thermally-induced HS to LS relaxation with T LIESST = 41 K.